Influence of data burst collision on transmission of AWS data through satellite - MUTHURAMALINGAM, E.; KUMAR, SANJAY; VASHISTHA, R. D. (MAUSAM, 2006)
lkj & Lopkfyr ekSle dsanz ¼,-MCY;w- ,l-½ og iz.kkyh gS ftlesa losndksa ds lkFk ml ks= dh mi iz.kkyh vkSj lapkj midj.k lEc) :Ik ls dk;Z djrs gSa tks Lopkfyr :Ik ls vkSj yxkrkj lgh le;kuqlkj ml LFkku dh ekSle dh fLFkfr;ksa dh eki djrs gSa rFkk ekSle foKku ds ekin.Mksa ds vuqlkj ?kaVkokj fy, x, izsk.kksa dks dasnz ls tqM+s mixzg ds kjk dsanzh; LVs’ku dks rhu ckj Lo;a fu/kkZfjr i)fr kjk vxyk izsk.k ysus ds iwoZ 60 feuV ds vUnj fu/kkZfjr 10&10 feuV ds vUrjky ij fcuk fdlh Øe ds vkHkklh ladsrksa dkss Hkstrs jgrs gSa A dHkh dHkh nks ;k vf/kd Lopkfyr ekSle dsanzksa ls vk¡dM+s ,d gh le; esa laizsf"kr gksus ij muds fefJzr gks tkus ds dkj.k ,- MCY;w- ,l- ds vk¡dM+s Bhd ls izkIr ugha gks ikrs gSa A eq[;r;k ,- MCY;w- ,l- ds vk¡dM+ksa dk lafeJ.k muds laizs"k.k ds le; vFkok laizs"k.k dh xfr latky esa ,- MCY;w- ,l- dh la[;k rFkk ,- MCY;w- ,l- ds vk¡dM+ksa ds lafeJ.k dh ek=k ij fuHkZj djrk gS A bl ’kks/k Ik= esa ,- MCY;w- ,l- ds vk¡dM+ksa ds mixzg ds ek/;e ls laizsf"kr vk¡dM+ksa ds lkFk vkil esa lafefJr gks tkus ls iM+us okys izHkko ds ckjs esa crk;k x;k gS A ” Automatic Weather Station (AWS) is a system consisting of sensors, associated field sub-systems and communication equipment, which automatically and continuously measure real time surface weather conditions and sends three times the hourly observed meteorological parameters to the central station through satellite link in a self timed pseudo random manner in its prescribed 10 minute time slot within the next 60 minutes before the next observation takes place. Loss of AWS data is due to collision of data burst transmitted simultaneously by any two or more AWS. Generally, the collision of AWS data burst depends upon the transmission time or transmission baud rate, number of AWS in a network and total number of bits in AWS data burst. This paper describes the influence of data burst collision on transmission of AWS data through satellite.